SUDAH SAMPAI MANA RISET ZAKAT KITA? - Aam Slamet Rusydiana; Salman Al-Farisi (Harmoni, 2016)
Zakat is one of the pillars of Islam. Not only Zakat has dimension of ritual but also social dimension. Meaning that, paying zakat (almsgiving) is not seen only as religious ritual but also it could touch humanity aspect by empowering its potency to maximize public wealth. On the other hand, the research related to zakat in Islamic economics area is still under study, if compared to the study of Islamic banking sector. This study tries to review a number of research on zakat. The study uses descriptive statistical analysis based on selected 120 journal publications related to zakat, both national and international journal. The entire sample is derived from academic journal that have been published in the last six years, from 2010 to 2015. The research shows that research on zakat is still dominated by the discussion of zakat institution (28%), followed by management of zakat (22%), zakat distribution (19%) and poverty (19%). The last theme is about zakat collection (13%). Malaysia and Indonesia became the highest zakat study area, while the majority of publications area is Indonesia, Malaysia and United States. In addition, the use of quantitative method and that of mixed methods is still low than the qualitative approach.